Supporting biodiversity: Structures of participatory actions in urban green spaces - Martens, Dörte; Öztürk, Öyküm; Rindt, Lara; Twarok, Jana; Steinhardt, Uta; Molitor, Heike (Frontiers in Sustainable Cities, 2022)
Biodiversity loss is an important topic considering climate change, global warming, and even the reasoning of current and future animal-related diseases, such as the COVID-19 pandemic. Urban biodiversity is also important because of the ecosystem services they provide, restorative benefits for well-being, and physical health of the people who live in urban areas. Each city has its own strategies to cope with this issue, and these strategies do not function without the contribution of habitants of the cities. We developed an index (BBS) of the existing possibilities to support urban biodiversity in Berlin to measure the awareness and willingness of the Berliners to participate and support urban biodiversity. A survey was conducted in a face-to-face situation in four districts of Berlin with 431 urban residents, measuring preference for three different levels of biodiversity, connectedness to residential greenspace, neighborhood and city, nature relatedness, and willingness in participatory actions around greenspace. The results show that the high biodiversity condition in a photo scenario was preferred by most residents, indicating the appreciation for urban biodiversity. The connectedness to the residential greenspace was high (and higher than the connectedness to neighborhood and city), showing large potential for quality of life. While the overall willingness to participate in actions to support urban greenspace was rather high, our index shows substantial differences in activities, which are perceived more or less. This is a key result for urban park management to increase urban biodiversity participation processes.